Arterial audiophotoplethysmography - Gammal, S. El; Lambotte, B.; Gammal, C. El; Blazek, V. (Phlebologie, 2003)
Background: Digital blood pressure is an important prognostic parameter in peripheral arterial disease. However, it is rarely determined in clinical routine because the methods available are too cumbersome. Patients and methods: Arterial audiophotoplethysmography (APPG) uses an in-built audio output. The systolic pressure corresponds to the reappearance of a pulssynchrone beep during deflation of the pressure cuff (25 mm wide on fingers and toes) after suprasystolic inflation. Measurements can be performed either in transmission or reflection mode. 50 healthy volunteers (age: 23-75 years) were examined in supine position. Blood pressure was taken at the A. brachialis, A. ulnaris, A. radialis, A. poplitea, A. tibialis anterior and posterior using ultrasound Doppler (USD), at the A. brachialis, fingers 1-5, A. poplitea and toes 1-3 using APPG. Results: Regarding the A. brachialis and poplitea, we found an excellent correlation between values obtained by USD and APPG in transmission mode (r: 0.92-0.99), the correlation with the reflection mode-values was slightly lower (r: 0.81- 0.93). The values obtained in reflection mode were significantly lower than in transmission mode (average 5.2 mmHg on the arms, 12.9 mmHg on the legs). Finger pressure was identical with A. brachialis-pressure. Toe/- brachial index was 0.81-0.86 (transmission) and 0.72- 0.78 (reflection). No significant difference was found between any of the fingers, respectively the toes. Conclusions: APPG is a reliable method for determination of digital blood pressure, which can be easily performed. Measurements in transmission mode should be preferred.
Keywords: Blood pressure; arteriosclerosis; ischemia; photoplethysmography